Heterogenous correlates of mechanization use and rural livelihoods in Zimbabwe: a quantile regression analysis - Ngoma, Hambulo; Mukamuri, Billy; Silva, João Vasco; Baudron, Frédéric (Elsevier, 2025)
The drive to mechanize and modernize African agriculture is in high gear, making the need for empirical evidence to guide mechanization investments critical. This paper assesses the heterogenous and distributional correlates of using mechanization and rural livelihoods in Chegutu and Zvimba districts of Zimbabwe, where a private sector company had the largest sales of different machinery across the country between 2019 and 2021. We used a quantile regression estimator and measured livelihoods using farm and household revenues. Based on survey data from 988 randomly selected households, we found that adoption was associated with rising land/labor ratio, market access and wealth. The use of mechanization was associated with a median annual increase of USD 262 in revenue with a wide range from USD 103 at the 25th percentile to USD 2,900 at the 95th percentile per year. The largest revenue gains were associated with post-harvest and irrigation equipment use, and in the upper percentiles of the revenue distribution. These findings call for (i) wealth agnostic promotional efforts to ensure equitable mechanization benefits, (ii) better targeting of mechanization types to farmer needs, and (iii) concerted efforts to strengthen mechanization service provision models.